Altered Glycosylation Contributes to Placental Dysfunction Upon Early Disruption of the NK Cell-DC Dynamics - Borowski, Sophia; Tirado-Gonzalez, Irene; Freitag, Nancy; Garcia, Mariana G.; Barrientos, Gabriela; Blois, Sandra M. (Frontiers in Immunology, 2020)
Immune cells (e.g. dendritic cells (DC) and natural killer (NK) cells) are critical players during the pre-placentation stage for successful mammalian pregnancy. Proper placental and fetal development relies on balanced DC-NK cell interactions regulating immune cell homing, maternal vascular expansion and trophoblast functions. Previously, we showed that in vivo disruption of the uterine NK cell-DC balance interferes with the decidualization process, with subsequent impact on placenta and fetal development leading to fetal growth restriction. Glycans are essential determinants of reproductive health and the glycocode expressed in a particular compartment (e.g. placenta) is highly dependent on the cell type and its developmental and pathological state. Here, we aimed to investigate the maternal and placental glycovariation during the pre- and post-placentation period associated with disruption of the NK cell-DC dynamics during early pregnancy. We observed that depletion of NK cells was associated with significant increases of O- and N-linked glycosylation and sialylation in the decidual vascular zone during the pre-placental period, followed by downregulation of core 1 and poly-LacNAc extended O-glycans and increased expression of branched N-glycans affecting mainly the placental giant cells and spongiotrophoblasts of the junctional zone. On the other hand, expansion of DC induced a milder increase of Tn antigen (truncated form of mucin-type O-glycans) and branched N-glycan expression in the vascular zone, with only modest changes in the glycosylation pattern during the post-placentation period. In both groups, this spatiotemporal variation in the glycosylation pattern of the implantation site was accompanied by corresponding changes in galectin 1 expression. Our results show that pre- and post- placentation implantation sites have a differential glycopattern upon disruption of the NK cell-DC dynamics, suggesting that immune imbalance early in gestation impacts placentation and fetal development by directly influencing the placental glycocode.